Synthesis, Characterization and Bioactivity of Subtituted Dithiocarbazate Schiff Bases of Acetylthiophenyl Isomer and Their Metal Complexes - Chan, Eddy Mun Hoe (2005)
The condensation reaction between S-benzyldithiocarbazate (SBDTC) and S-methyldithiocarbazate (SMDTC) and acetylthiophene isomers (2- acetytthiophene and 3-acetytthiophene) to produce benzyl N-[I-(thiophen-2- yl)ethylidene] hydrazine carbodithioate (SBZATP), benzyl N-[I-(thiophen-3- yl)ethylidene] hydrazine carbodithioate (SB3ATP), methyl N-[1-(thiophen-2- yl)ethylidene] hydrazine carbodithioate (SMZATP) and methyl N-[1-(thiophen- 3-yl)ethylidene] hydrazine carbodithioate (SMZATP) has been carried out. Cobalt (II), nickel (II), copper (II), zinc (11) and cadmium (11) complexes of the synthesized Schiff bases were prepared. AH the compounds were characterized by standard physico-chemical techniques and in addition, single crystal x-ray analyses were done where possible. Antimicrobial activity and cytotoxic assays were carried out using the synthesized Schiff bases and their metal complexes. Four target microbes and four fungi were used in the antimicrobial adivtty studies and five target cancer cell lines were used for the cytotoxic assays. The SBZATP, SB3ATP, SMZATP and SM3ATP coordinate to Co(ll), Ni(l I), Cu(ll), Zn(1l) and Cd(1 I) ion as uninegatively charged bidentate ligands. All complexes are non-electrolytes in DMSO. Magnetic moments and electronic spectra show that the Cu(ll) complexes are paramagnetic compounds with distorted square planar structures while the Ni(SB2ATP)2 are diamagnetic with distorted square planar environments. The structure of SB2ATP was solved in a tridinic crystal class with a P -1 space group while the SMZATP was solved in a monoclinic crystal class and with a P 2,Ic space group. The Ni(SB2ATP)2 (monoclinic, P 2/c ) contains four-coordinated nickel(l1) in non-planar environment as a distorted square planar monomeric entity. The crystal system of Ni(SMZATP)2 is monoclinic of space group P 2&. This asymmetric unit consists of 2 molecules. The two bidentate ligands are coordinated to the nickel atom through an azomethine nitrogen and thiolo sulfur in a distorted tetrahedral environment around the nickel atom. In general, it is clearly seen that the thiophene Schiff bases and their metal complexes do not inhibit the growth of fungi except for SB2ATP and its Cu(ll) complex, which showed antifungal activity towards Candida lypolytica (2075) only. With the exception of CU(SM~ATP)w~h, ich is active against Methicillin resistant staphylococcus (MRSA), Bacillus subtilis-wild type (B29) and S. Typhimurium (S.T.), the thiophene Schiff bases and their metal complexes are inactive. It can be concluded that chelation of Cu(ll) ion increases the antifungal activity of the Schiff bases towards the target microbes. The compounds synthesized were particularly active against human breast carcinoma with positive estrogen receptor (MCF-7). However, there was only slight activlty towards the human myeloid leukemia (HL-60) cell line. The remainder of the cell lines are not responsive to the compounds.